Legacy effects of drought alters the aquatic food web of a northern boreal peatland. (6th June 2017) - DeColibus, Dawn T.; Rober, Allison R.; Sampson, Avery M.; Shurzinske, Amanda C.; Walls, Jeremy T.; Turetsky, Merritt R.; Wyatt, Kevin H.
Abstract: Compared to other temporary aquatic ecosystems, we know relatively little about how inundation frequency and duration (i.e. hydrologic regime) influences the structure of aquatic communities in northern peatlands. In this study, we examined patterns in nutrient availability and aquatic community structure during a natural flooding event in an Alaskan fen where water‐table position had been manipulated in three large‐scale experimental plots during previous years to simulate both drought (lowered water‐table treatment) and flooding (raised water‐table treatment) conditions relative to a control without manipulation. Although the natural flood disrupted the long‐term experimental manipulation, it provided an opportunity to evaluate how variation in past hydrologic regime influences nutrient dynamics and aquatic food web structure during periods of inundation in a northern boreal peatland. Despite similar water depth among experimental plots during the time of sampling (i.e. water was above the peat surface in all plots), water‐column nutrient concentrations were significantly greater in the drought treatment (where water table had been lowered during the previous growing season) compared to the raised water‐table treatment and the control. Algal production increased with enhanced nutrient availability across all water‐table treatments and was most elevated following the rewetting of dry sediments in the drought treatment. Consumer biomass (heterotrophic bacteria and macroinvertebrates) increased with algal production and was significantly greater in the drought treatment compared to the raised water‐table treatment and the control. Consumer biomass decreased into the second year of constant inundation as algal production was constrained by reduced nutrient availability. Stable isotope analysis ( 13 C and 15 N) showed that elevated levels of periphyton (i.e. the intact biofilm) associated with enhanced nutrient availability promoted energy transfer to higher trophic levels (grazers and predators) rather than living or dead mosses or vascular plant material. Consumption of algal material by grazers altered the size and composition of the algal community. The algal community shifted from coccoid (edible) to filamentous (inedible) growth forms with increased grazer abundance in the drought treatment, possibly owing to selective grazing. Conversely, there was a similar proportion of edible and inedible taxa in the control and raised treatments where grazers were lower in abundance. Our results show that the legacy effects of drought can regulate aquatic community structure in northern peatlands. Within a predictive context, our findings suggest that conditions of more variable hydrology expected with climate change (i.e. increased frequency of drought) occurring across northern latitudes will promote energy flow to higher trophic levels by releasing nutrient constraints on microalgae during periods of inundation.